Cotton and Surgical Face Masks in Community Settings: Bacterial Contamination and Face Mask Hygiene - Delanghe, Lize; Cauwenberghs, Eline; Spacova, Irina; De Boeck, Ilke; Van Beeck, Wannes; Pepermans, Koen; Claes, Ingmar; Vandenheuvel, Dieter; Verhoeven, Veronique; Lebeer, Sarah (Frontiers in Medicine, 2021)
During the current COVID-19 pandemic, the use of face masks has become increasingly recommended and even mandatory in community settings. To evaluate the risk of bacterial cross-contamination, this study analyzed the bacterial bioburden of disposable surgical masks and homemade cotton masks, and surveyed the habits and face mask preferences of the Flemish population. Using culture approaches and 16S rRNA gene amplicon sequencing, we analyzed the microbial community on surgical and/or cotton face masks of 13 healthy volunteers after four hours of wearing. Cotton and surgical masks contained on average 1.46x105 CFU/mask and 1.32x104 CFU/mask respectively. Bacillus, Staphylococcus and Acinetobacter spp. were mostly cultured from the masks and 43% of these isolates were resistant to ampicillin or erythromycin. Microbial profiling demonstrated a consistent difference between mask types. Cotton masks mainly contained Roseomonas, Paracoccus and Enhydrobacter taxa and surgical masks Streptococcus and Staphylococcus. After four hours of mask wearing, the microbiome of the anterior nares and the cheek showed a trend towards an altered beta-diversity based. According to dedicated questions in the large-scale Corona survey of the University of Antwerp with almost 25,000 participants, only 21% of responders reported to clean their cotton face mask daily. Laboratory results indicated that the best mask cleaning methods were boiling at 100° C, washing at 60° C with detergent or ironing with a steam iron. Taken together, this study suggests that a considerable number of bacteria, including pathobionts and antibiotic resistant bacteria, accumulate on surgical and even more on cotton face masks after use. Based on our results, face masks should be properly disposed of or sterilized after intensive use. Clear guidelines for the general population are crucial to reduce the bacteria-related biosafety risk of face masks, and measures such as physical distancing and increased ventilation should not be neglected when promoting face mask use.